2020
DOI: 10.1111/ijn.12844
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, attitudes and behaviours of Syrian refugee women towards family planning: Sample of Hatay

Abstract: Objective This study was conducted with the aim of determining the fertility characteristics of Syrian refugee women and their knowledge, attitudes and behaviours with regard to family planning. Design and Sample The research was designed as a descriptive and cross‐sectional type of study. The study group consisted of 389 refugee women in the 15‐ to 49‐year age group who had migrated from Syria to Hatay. Measure Study data were collected between October 2018 and January 2019 using forms containing questions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…23,24 It has been shown that the modern methods that Syrian women know the most are pills, condoms, and IUDs, and the traditional method they know best is CI. 25,26 In general, it has been shown that many factors affect the perspective of Syrian refugees towards FP methods, such as age, education level, income level, traditions and belief systems, and the use of modern methods increases as age, education, and income lev-els increase: [25][26][27] In their studies evaluating the knowledge, attitudes, and behaviors of 389 Syrian women on FP, Gümüş Şekerci et al reported that more than half of the participants did not know what FP meant, but well-educated women aged 35 years and over preferred modern methods. 25 In this study, Syrian women preferred modern birth control methods rather than traditional methods such as CI.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 It has been shown that the modern methods that Syrian women know the most are pills, condoms, and IUDs, and the traditional method they know best is CI. 25,26 In general, it has been shown that many factors affect the perspective of Syrian refugees towards FP methods, such as age, education level, income level, traditions and belief systems, and the use of modern methods increases as age, education, and income lev-els increase: [25][26][27] In their studies evaluating the knowledge, attitudes, and behaviors of 389 Syrian women on FP, Gümüş Şekerci et al reported that more than half of the participants did not know what FP meant, but well-educated women aged 35 years and over preferred modern methods. 25 In this study, Syrian women preferred modern birth control methods rather than traditional methods such as CI.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong need for the beliefs about the side effects of the use of contraceptives in refugees to be broken, for wrong beliefs concerning the application of FP to be removed (23,24) and for the negative attitude to girl children to be eliminated (4,12). Education campaigns should be conducted to provide information on the correct use and timing of these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Personal Information Form: This form was devised by the researchers by scanning the literature (4,9,11,14), and consisted of 25 questions on age, education level, profession, husband's profession, income status, family structure, social security, smoking, chronic illness and obstetric characteristics, and assessed the level of knowledge of family planning, sources of information, methods used and frequency of use.…”
Section: Data Collection Formmentioning
confidence: 99%
See 2 more Smart Citations